2002
DOI: 10.1128/jvi.76.3.1062-1070.2002
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Avian Myelomonocytic Growth Factor in Infection with Marek’s Disease Virus

Abstract: Marek's disease virus (MDV) is a herpesvirus that induces T lymphomas in chickens.The aim of this study was to assess the role of the macrophage activator chicken myelomonocytic growth factor (cMGF) in controlling MDV infection. B13/B13 chickens, which are highly susceptible to MD, were either treated with cMGF delivered via a live fowlpox virus (fp/cMGF) or treated with the parent vector (fp/M3) or were left as untreated controls. Seven days later, when challenged with the very virulent RB-1B strain of MDV, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Birds vaccinated with HVT alone suffered 33% mortality whereas vaccinated birds that were treated with cMGF had no mortality (Figure 4). These results showed improved protection with the vaccine and less tumour incidence in MDV‐challenged birds 52 , and clearly indicates the potential use of cMGF as a vaccine adjuvant for viral strains used in vaccines to increase protection against MDV.…”
Section: Chicken Cytokines As Potential Adjuvantsmentioning
confidence: 68%
See 1 more Smart Citation
“…Birds vaccinated with HVT alone suffered 33% mortality whereas vaccinated birds that were treated with cMGF had no mortality (Figure 4). These results showed improved protection with the vaccine and less tumour incidence in MDV‐challenged birds 52 , and clearly indicates the potential use of cMGF as a vaccine adjuvant for viral strains used in vaccines to increase protection against MDV.…”
Section: Chicken Cytokines As Potential Adjuvantsmentioning
confidence: 68%
“…The in vivo biological activity of cMGF delivered via a live fowlpox virus (fp/cMGF) had been demonstrated in a previous study 51 . A more recent study has indicated the adjuvant potential of cMGF 52 . Birds highly susceptible to Marek's disease virus (MDV) were treated with fp/cMGF.…”
Section: Chicken Cytokines As Potential Adjuvantsmentioning
confidence: 99%
“…The conditions included denaturation at 94°C for 1 min, annealing at 60°C for 30 s, and extension at 72°C for 1 min using primers for Tβ‐4, IL‐6, and inducible nitric oxide synthase (iNOS) along with β‐actin as the reference gene 10 . The primers were designed with the Primer 3 software program 11 from the coding sequences of chicken Tβ‐4 (Genbank Accession NM 001001315 12 ), IL‐6 (Genbank accession AJ309540 13 ), and iNOS (Genbank accession U46504 14, 15 ). The primer sequences for Tβ‐4 were: forward: 5′ GCCGAGATCGAGAAATTTGA 3′; reverse: 5′ GAAGGCAATGCTTGTGGAAT 3′.…”
Section: Methodsmentioning
confidence: 99%
“…Combinations of HVT and glutaraldehyde-inactivated serotype 1 MDV obtained from feather follicles was reported to improve protection (Pruthi et al, 1987). Several studies have been conducted to include cytokines in MD vaccines to enhance the cellular immune response (Djeraba et al, 2002;Tarpey et al, 2007). The mechanisms involved are poorly understood and represent an overlooked but important area for future research.…”
Section: • Vaccine Administrationmentioning
confidence: 99%